The qualitative method for a humanisation of research - Artioli, Giovanna; Sarli, Leopoldo (Acta Biomedica Atenei Parmensis, 2021)
Huge progress in scientific research, added to vast investments, have allowed to develop vaccines against the virus responsible for Sars-Cov-2 in times unimaginable, until recently (1). The use of these vaccines has documented their high efficacy and very low risk of adverse events. Undergoing vaccination campaigns around the world are changing the history of the COVID-19 pandemic. Never before has scientific research been a topic of widespread interest as in this period. [...]